Pre-Service Teachers Adaptability in The Philippines during Student Exchange Program - Maria Anggelinawati; Effendi Limbong; Ventje Jany Kalukar (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2024)
This research investigates the adaptability skills of pre-service teachers during a student exchange program in the Philippines, focusing on their development and challenges in a new cultural and academic setting. Through qualitative methods, findings highlight cognitive, emotional, and behavioral adaptability, as three participants overcame language barriers, culture shock, and logistical issues. Despite challenges in STEM teaching, cultural norms, and infrastructure, these experiences fostered significant personal and professional growth. The study underscores the transformative role of exchange program in preparing teachers for diverse educational contexts and offers recommendations for stakeholders to enhance program effectiveness.